2010
DOI: 10.1007/s00421-010-1716-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metaboreflex activation by static exercise dilates pupil in humans

Abstract: We examined a hypothesis that static exercise and activation of sympathetic activation by metabolically sensitive skeletal muscle afferents (metaboreflex) influence the sympathetic nervous activity modulating pupil diameter. Nine subjects performed 2 min isometric handgrip exercise at 30% maximal voluntary contraction, which was followed by either 2 min of postexercise muscle ischemia (PEMI) in the forearm or no PEMI (control trial). The pupil diameter and mean blood pressure (MAP) increased significantly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…We also assessed the data using the handgrip-specific top-20 pupil diameter value method [9]. In a repeated measures ANOVA, there were no significant differences in the top-20 pupil response to the handgrip and the control block (F (1, 48) = .33, p > 0.1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also assessed the data using the handgrip-specific top-20 pupil diameter value method [9]. In a repeated measures ANOVA, there were no significant differences in the top-20 pupil response to the handgrip and the control block (F (1, 48) = .33, p > 0.1).…”
Section: Resultsmentioning
confidence: 99%
“…We selected this measure for analysis because pupil dilation is considered a reliable measure of sympathetic arousal [33, 34]. Also, a recent study with isometric handgrip showed pupil diameter increased in response to a 2-min isometric handgrip task [9]. Fixation events and pupil dilation data for each participant were exported using the eye-tracking analysis software program BeGaze 2 (SensoMotoric Instruments).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations